Improvement of specific energy absorption of composite tubular absorbers using various stitching pattern designs - Rabiee, Ali; Ghasemnejad, Hessam (Springer, 2020)
In this paper, various patterns of multi-stitched locations were studied experimentally and numerically to improve the specific energy absorption (SEA) in composite tubular absorbers. In this regard, stitching patterns with a horizontal distance of 3 mm, 6 mm, 9 mm and 18 mm in straight and zig-zag designs were investigated to justify their effect on mean crushing force and energy absorption capability. A multi-shell configuration finite element model is also developed based on energy-based contact definitions, which considers the delamination in Mode-I and stitching pattern design to accurately predict the energy absorption capability and axial crushing behaviour of composite crash absorbers, At stitched locations, the critical normal surface separation was utilised concerning experimental data to improve delamination resistance. The multi-stitching rows of 10–15-20–25-30–35 mm with 3 mm horizontal and 2.5 mm vertical distances between each stitched point can increase the specific energy absorption up to 32% in comparison with non-stitched specimens. The developed numerical model for multi-layered composites absorbers in comparison with the existing methods is efficient in terms of accuracy with less than 5% error in comparison with experimental data.
Keywords: Energy Absorption; Composites; Multi-stitching; Pattern; PARAM